Development and Validation of a Protocol for Pregnant Women Based on the Brazilian Dietary Guidelines - Cláudia Raulino Tramontt; Juliana Giaj Levra de Jesus; Thanise Sabrina Souza Santos; Fernanda Rauber; Maria Laura da Costa Louzada; Vanessa Del Castillo Couto; Jacqueline Resende Berriel Hochberg; Patrícia Constante Jaime (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective To develop and validate a protocol for the use of the Dietary Guidelines for the Brazilian Population (DGBP) in the individual dietary advice for pregnant women assisted in primary healthcare (PHC). Methods Methodological study that involved the elaboration of a protocol in six steps: definition of the format, definition of the instrument to evaluate food consumption, systematization of evidence on food and nutrition needs of pregnant women, extraction of DGBP recommendations, development of messages of dietary guidelines and content, and face validity. The analyses of the validation steps were carried out by calculating the Content Validity Index (CVI) and thematic content analysis. Results As products of the steps, the protocol structure was defined and the dietary advice for pregnant women were elaborated, considering physiological changes, food consumption, nutritional and health needs, and socioeconomic conditions of this population. The protocol was well evaluated by experts and health professionals in terms of clarity, relevance (CVI > 0.8), and applicability. In addition, the participants made some suggestions to improve the clarity of the messages and to expand the applicability of the instrument with Brazilian pregnant women. Conclusion The instrument developed fills a gap in clinical protocols on dietary advice for pregnant women focused on promoting a healthy diet, contributing to a healthy pregnancy. In addition, it demonstrates potential to contribute to the qualification of PHC professionals and to the implementation of the DGBP recommendations.